QUICK-HEAL SYNDROME: AN INSIGHT INTO THE MENACE OF SELF-MEDICATION AMONG STUDENTS OF FEDERAL UNIVERSITY BIRNIN KEBBI - Mohammed, Ismaila; Ibrahim Muhammad, Yahaya; Garba Yauri, Muhammad (African Journal of Social and Behavioural Sciences, 2024)
The purpose of this study is to assess the issue of self-medication among students at Federal University Birnin Kebbi, Kebbi State, Nigeria. University students often engage in the unofficial procurement of drugs from medical shops when they experience health issues. A significant concern is that some of these drugs are sold to students by individuals with little to no formal medical training, including underage children who are under 18 years of age. These individuals may lack the necessary knowledge about proper dosage and prescriptions. Instead of utilizing the university’s health facilities, many off-campus students prefer self- medication, likely because of the proximity of drug stores. This descriptive study involved 254 students selected via a stratified sampling technique. The findings reveal that the majority of students engage in self-medication, primarily on the basis of their own experiences. As a result, when they perceive a health issue, they often travel directly to a nearby drug store and request specific medications. This behaviour is most prevalent among students living off campus, underscoring the role of proximity in their choices. The health belief model was used as the theoretical framework to analyse this issue. The study recommends that the university administration or student unions organize seminars to educate students about the short- and long-term effects of self-medication, as many students are unaware of the potential negative consequences. Additionally, government agencies should take action to shut down unlicensed drug stores.